Dependency analysis approach for managing supply chain flexibility. (4th January 2010) - More, Dileep; Subash Babu, A.
For managing flexibility in the supply chain (SC), characterising, representing and analysing dependencies in the chain are essential at system level. However, it is a complex and multifaceted task. In this paper an attempt is made to develop a systematic approach for specifying, quantifying, analysing and managing various types of dependencies in the SC, in the context of SC flexibility. The framework uses known concepts like system thinking (CATWOE), process views (SCOR model) and dependency structure matrix (DSM) systematically. Moreover, a number of dependency indices were proposed for studying a typical supply chain which is found to be useful in identifying the critical player, the critical players' relative position and the critical segments of the SC. The approach developed is explained with the help of an example.